Inisiasi Pembentukan Angkatan Siber dan Digital dalam Organisasi Tentara Nasional Indonesia - Nurmaida Delviana (Jurnal Syntax Admiration, 2024)
In the era of digital transformation, every country in the world must be able to adapt and adopt these changes as a strategy to strengthen national defense because cyberspace in relation to international relations can be a source of various potential threats, vulnerabilities, and insecurity in the international order. China recognized the importance of AI in shaping the future global economic, military and geopolitical environment, and launched the "Next Generation Artificial Intelligence Development Plan." which aims to become a global leader in AI by 2030. The research method used is prescriptive analysis and qualitative data analysis. Based on the results of the study, there are 4 (four) important points to realize this, namely the alignment of regulations related to cyber and digital in Indonesia with the initiation with revisions both in the form of proposed new articles and / or reviews in Law Number 34 of 2004 concerning the Indonesian National Army, then digital infrastructure development in Indonesia, digital literacy development in Indonesia, and appropriate personnel mobilization strategies based on the state of human resources in Indonesia.